The dimensions and consequences of trust in senior management - Albrecht, Simon L. (Curtin University, 2001)
Trust between individuals and groups has been identified as an important factor in determining organisational success, organisational stability and the well-being of employees. The present research contributes to the growing literature on trust by developing measures and models of how employees trust senior management. Drawing from the literature and the results of pilot studies, a six dimensional model of trust in senior management - consisting of dispositional, cognitive, affective, social and behavioural intent dimensions - was tested using confirmatory factor analysis (n = 416). The results clearly supported the convergent and discriminant validity of the measurement model. For example, all model fit indices were above minimum recommended values and all items loaded at significant levels on their specified factor.The measures were successfully cross- validated in a sample from a different organization (n = 249). Next, models portraying alternative structural relations between the dimensions were examined, before deriving a model which successfully summarized the data in a theoretically plausible way. The model showed trust in senior management, defined in terms of behavioural intentions, to be directly influenced by affective reactions and perceived social norms. Cognitive assessments about the overall effectiveness of senior management were shown to have an indirect influence on trust. This structural model was successfully cross- validated on an independent sample. The attitudinal dimensions of the model were shown to hold, longitudinally, over a twelve month period (n = 257).In contrast to previous cross-sectional research, disposition did not influence trust in senior management over time. In terms of determining the organizational consequences of trust in senior management, the results showed that trust in senior management influenced cynicism toward change over a twelve month time period. Theoretical implications and the practical implications for the diagnosis and management of trust in senior management are discussed.